Macdonald, The History Shoppe - Faegin, Jayme (Teaching History: A Journal of Methods, 2010)
The question at the center of J. Fred MacDonald's e-book The History Shoppe is a familiar one for most history teachers. More often than not, students come to survey-level courses with the misconception that history is all about the memorization of obscure facts. MacDonald offers an alternative. The narrative begins when Scott Tennyson, a high school student who fancies himself the "King of History," unexpectedly stumbles upon a mysterious store called "The History Shoppe." Inside, he encounters an intriguing gentleman, Dr. Papadopoulos, who tells Scott that history is not about memorizing disparate facts, but rather about understanding and interpreting the past. Dr. Pop introduce his young student to a special machine, Clio, that transports its passengers into the production world of any film they choose. Scott visits Guernsey in the early years of World War II, explores the United States during the 1950s, and finds himself squarely in the middle of the political minefield that was the New Deal, as he seeks to formulate an answer to the question posed by countless history teachers: What is history?